Revisiting rurality and schooling: A teacher’s story - Daisy Pillay; Sheeren Saloojee (Perspectives in Education, 2012)
This paper presents an understanding of what it means to be a teacher in a school defined as ‘rural’. From a sociological perspective, we consider the mechanisms and ways of knowing that are adopted by a teacher for understanding not only the external world but for being a certain kind of teacher for a school in a rural setting. Employing data techniques from life history and collage compositions, data was produced with a teacher we have named Hilton. The data focused on his daily lived experiences and the social realities of working in the context of rural education to offer an expanded social and collective approach to teacher identity. Through his story, as told and experienced by him, we foreground dominant discourses at work in a rural context, and show how specific discourses define Hilton’s life and work as a teacher in specific ways. Despite the challenges and adversities he faces, we show how as a teacher he chooses to negotiate - through resistance and complicity - the discourses that dominate rural schooling and its culture, learners, teachers and communities. The article concludes that a teacher’s capacity to disrupt and challenge stereotypical meanings of rural schooling involves ongoing dialogue with the self, with teachers, with learners and the wider community.